Humanistic Psychotherapies: Handbook of Research and Practice. 2002
DOI: 10.1037/10439-003
|View full text |Cite
|
Sign up to set email alerts
|

Process–outcome research on humanistic therapy variables.

Abstract: Process-outcome research on humanistic therapies, particularly clientcentered and experiential therapies (CC/ET), has a long tradition. Initiated by Rogers (1957) and continued by Barrett-Lennard (1962) and Truax 83

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 79 publications
3
25
0
3
Order By: Relevance
“…Goldman, Greenberg, and Pos (2005) found that positive shifts in the quality of clients' exploration of their inner experience--as measured by the Client Experiencing Scale (Klein, Mathieu, Gendlin, & Kiesler, 1969)--was a stronger predictor of outcome than the working alliance in client-centered and emotion-focused psychotherapy for depression. Previous studies have also addressed the impact of therapist proposals on the depth of clients' self-exploration (Sachse, 1992;Sachse & Elliott, 2002) in therapy sessions and found that therapists' statements that were high in experiencing resulted in higher levels of clients' experiencing during therapy sessions and that the depth of therapist experiential focus predicted overall outcome (Adams & Greenberg, 1996).…”
Section: Qualitative Hprmentioning
confidence: 97%
“…Goldman, Greenberg, and Pos (2005) found that positive shifts in the quality of clients' exploration of their inner experience--as measured by the Client Experiencing Scale (Klein, Mathieu, Gendlin, & Kiesler, 1969)--was a stronger predictor of outcome than the working alliance in client-centered and emotion-focused psychotherapy for depression. Previous studies have also addressed the impact of therapist proposals on the depth of clients' self-exploration (Sachse, 1992;Sachse & Elliott, 2002) in therapy sessions and found that therapists' statements that were high in experiencing resulted in higher levels of clients' experiencing during therapy sessions and that the depth of therapist experiential focus predicted overall outcome (Adams & Greenberg, 1996).…”
Section: Qualitative Hprmentioning
confidence: 97%
“…Every mode of therapy has adopted the notion of empathy and considers it to be a relevant basic condition (Sachse & Elliott, 2002;Watson, 2002). The taken-for-granted nature of empathy as an essential background condition has led many therapists to conceive of it as hardly more than a kindly and supportive presence (Bohart & Greenberg, 1997;Snyder, 1992).…”
Section: Contemporary Understandings Of Empathymentioning
confidence: 99%
“…Microprocess research (e.g., Sachse & Elliott, 2001) focuses on the impact of single interventions. Using transcripts of client-therapist-client (CTC) interactions, observers rate whether or not interventions encourage deeper exploration or integration of problematic experiences.…”
Section: Microprocess Research and Process Markersmentioning
confidence: 99%